2007
DOI: 10.1016/j.neuropharm.2007.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting demonstrates that α4 nicotinic acetylcholine receptor subunits contribute to expression of diverse [3H]epibatidine binding sites and components of biphasic 86Rb+ efflux with high and low sensitivity to stimulation by acetylcholine

Abstract: [3H]Epibatidine binds to nAChR subtypes in mouse brain with higher (KD approximately 0.02 nM) and lower affinity (KD approximately 7 nM), which can be further subdivided through inhibition by selected agonists and antagonists. These subsets are differentially affected by targeted deletion of alpha7, beta2 or beta4 subunits. Most, but not all, higher and lower affinity binding sites require beta2 (Marks, M.J., Whiteaker, P., Collins, A.C., 2006. Deletion of the alpha7, beta2 or beta4 nicotinic receptor subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…In a study by Marks et al (1998), [ 3 H]epibatidine showed monophasic binding to 12 different mouse brain regions, however, displacement with reference compounds including ACh, nicotine and cytisine revealed biphasic displacement properties, suggesting different receptor populations. Similar expression patterns have been observed in rat, human (Houghtling et al, 1995;Davila-Garcia et al, 1997) and mouse brain tissue (Marks et al, 1998) and much effort has been invested in determining which nAChR subpopulations constitute the collective binding using pharmacological methods and gene knockout techniques (Marks et al, 2010(Marks et al, , 2006(Marks et al, , 2007. Approximately 50% of total brain binding consists of high affinity sites (K d~2 0 pM) whereas the other 50% are sites of significantly lower affinity (K d~5 nM).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In a study by Marks et al (1998), [ 3 H]epibatidine showed monophasic binding to 12 different mouse brain regions, however, displacement with reference compounds including ACh, nicotine and cytisine revealed biphasic displacement properties, suggesting different receptor populations. Similar expression patterns have been observed in rat, human (Houghtling et al, 1995;Davila-Garcia et al, 1997) and mouse brain tissue (Marks et al, 1998) and much effort has been invested in determining which nAChR subpopulations constitute the collective binding using pharmacological methods and gene knockout techniques (Marks et al, 2010(Marks et al, , 2006(Marks et al, , 2007. Approximately 50% of total brain binding consists of high affinity sites (K d~2 0 pM) whereas the other 50% are sites of significantly lower affinity (K d~5 nM).…”
Section: Discussionmentioning
confidence: 56%
“…Peculiarly, these populations are dependent on expression of b2, a4 or b4 subunits and their expression pattern resembles that of a4b2 receptors (Marks et al, 2010). Several speculations have been put forward to explain the existence of these low affinity a4 and b2 dependent sites including stoichiometry dependency (2a:3b vs. 3a:2b), state dependency (resting vs. desensitized), improperly assembled receptors or complex mixtures of receptors incorporating more than two different subunits (Person and Wells, 2011;Marks et al, 2007). The recent knowledge that 3a:2b receptors harbor an orthosteric aea interface suggests an alternative explanation.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that dopamine release mediated by the ␣CtxMII-resistant subtypes is affected by the S248F mutation, whereas release mediated by the ␣CtxMII-sensitive subtypes does not differ with genotype. 86 Rb ϩ efflux is mediated by two populations of nAChRs, a low-and a highaffinity form, both thought to be ␣4␤2* subtypes (Marks et al, 2007). In addition, […”
Section: S248f Knock-in Mice Display Altered Synaptosomal Nachrs Funcmentioning
confidence: 99%
“…We have developed and characterized an assay that measures a biphasic agonist-stimulated 86 Rb + efflux from mouse brain synaptosomes (Marks et al 1999). Both HS and LS responses are clearly mediated by α4β2* nAChRs, given that all response is absent from synaptosomes obtained from α4 (Marks et al 2007) and β2 (Marks et al 2000) null mutant mice. Some of the HS response is also mediated by the α4α5β2-nAChR, given that α5 null mutation results in a decrease in agonist efficacy for the higher sensitivity efflux (Brown et al 2007).…”
Section: Introductionmentioning
confidence: 97%